2004
DOI: 10.1007/s00268-003-7304-1
|View full text |Cite
|
Sign up to set email alerts
|

Sternocleidomastoid Muscle Flap Preventing Frey Syndrome following Parotidectomy

Abstract: Frey syndrome is one of the potential sequelae of parotidectomy. Various medical and surgical treatments have been used in an attempt to avoid this embarrassing condition. Recently, interposing barriers between the overlying skin flap and the parotid bed, such as the sternocleidomastoid muscle (SCM) flap, have been used to prevent this condition. The purpose of this study was to evaluate the impact of using this flap on Frey syndrome. A series of 138 patients who underwent subtotal or total parotidectomy from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
1
28
1
2
Order By: Relevance
“…In this paper we found FS positiveness in 21% of the patients who underwent partial parotidectomy, in agreement with literature results that indicate partial parotidectomy as proper treatment for benign parotid tumors 14,15 , and corroborating the already reported surgical approaches to reduce FS, such as rotating the sternocleidomastoid muscle flap 16 .…”
Section: Discussionsupporting
confidence: 80%
“…In this paper we found FS positiveness in 21% of the patients who underwent partial parotidectomy, in agreement with literature results that indicate partial parotidectomy as proper treatment for benign parotid tumors 14,15 , and corroborating the already reported surgical approaches to reduce FS, such as rotating the sternocleidomastoid muscle flap 16 .…”
Section: Discussionsupporting
confidence: 80%
“…27 In contrary, some other studies found a significant lower incidence of symptomatic Frey syndrome after parotidectomy in patients in whom a superiorly or inferiorly based sternocleidomastoid muscle flap was used as compared with those without. 24,28,29 This difference in incidence of Frey syndrome could not be confirmed in all studies in which a sternocleidomastoid flap interposition was used (Table 1). [30][31][32] Moreover, the incidence of abnormal greater auricular nerve function and abnormal facial sensation was higher in patients who underwent this interposition.…”
Section: Quality Of Lifecontrasting
confidence: 62%
“…Techniques such as sternocleidomastoid (SCM) muscle flaps, superficial musculoaponeurotic system (SMAS) interposition, and artificial implants have been described with varying degrees of success. [4][5][6] This work is a metaanalysis of published studies of proposed methods for minimizing facial contour defects and Frey syndrome after superficial parotidectomy.…”
Section: Arch Facial Plast Surg 2009;11(5):327-331mentioning
confidence: 99%